History of Law 6, 1991 - Galindo, Manuel Antonio (Colombian Journal of Anesthesiology, 2022)
Law 6 was enacted thirty years ago. Notwithstanding the fact that almost three decades have elapsed, with the exception of the regional and national leaders, many anesthesiologists are unaware of the existence of such law, of its contents or about which are the positive aspects for the specialty and for all anesthesia colleagues. There is a lack of awareness regarding the fact that the oversight committees are a valuable instrument to ensure excellence in the practice of anesthesia. This publication shall contribute to an share an overview of the efforts made to ensure the approval of the Law by the National Congress and of the Law among all anesthesiologists in the country. In this way, all practitioners will become acquainted with the information on the topic to take advantage of the provisions in the Law.